Novel trifluoromethylpyridine piperazine derivatives as potential plant activators - Zhang, Wei; Guo, Shengxin; Wang, Ya; Tu, Hong; Yu, Lijiao; Zhao, Zhichao; Wang, Zhenchao; Wu, Jian (Frontiers in Plant Science, 2022)
A series of novel trifluoromethylpyridine linked piperazine derivatives (A1−A27) were designed and synthesized. The in vivo anti-viral activity of the analogs was tested against tobacco mosaic virus (TMV) and cucumber mosaic virus (CMV) which revealed that a the synthesized (A1, A2, A3, A9, A10, A16, A17, and A21) compounds possessed higher activity than commercialized ningnanmycin. Particuarly, the in vivo antiviral activity indicated compound A16 showed the most potent protective activity toward TMV (EC50 = 18.4 µg/mL) and CMV (EC50 = 347.8 µg/mL), compared to ningnanmycin (50.2 µg/mL for TMV, 359.6 µg/mL for CMV). Excitingly, further studies revealed that compound A16 could enhance the defensive enzyme activities of superoxide dismutase (SOD), polyphenol oxidase (PPO) and phenylalanine ammonialyase (PAL), and activate the phenylpropanoid biosynthesis pathway to enhance the antiviral activities of tobacco. This study provides reliable support for the development of new antiviral pesticides and their potential antiviral mechanisms.